Improving the Quality of Islamic Education Learning through the Method of Giving Learning Assignments and Recitations at SD Negeri 5 Manggeng - Zuraida; Azizah, Nur (Journal of Indonesian Primary School, 2025)
This study aims to improve student learning in Islamic religious education learning by using the assignment and recitation method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the assignment and recitation method can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 49.71%, the first cycle 76.39% and in the second cycle it increased to 93.16%. Thus, the use of the assignment and recitation method can be used as an alternative to improve student learning outcomes in Islamic religious education learning.